Comparison of pneumococcal conjugate vaccine (PCV-13) cellular immune responses after primary and booster doses of vaccine - Timothy J. Chapman; Michael E. Pichichero; Ravinder Kaur (Taylor & Francis Group, 2020)
Since their widespread use, pneumococcal conjugate vaccines (PCVs) have proven effective at reducing both invasive and noninvasive pneumococcal diseases and nasopharyngeal carriage of Streptococcus pneumoniae (Spn). To establish this level of protection, a three-dose schedule with a single booster (3 + 1) was the immunization regime in the USA. Alternatively, WHO-approved schedules of 3 + 0 and 2 + 1 are now becoming adopted in many countries to reduce the cost of vaccination. Sustained protection from pneumococcal disease and carriage requires persisting levels of antibody and cellular immune memory. Although antibody responses to PCVs are well studied, less is known concerning the cellular response to the vaccine in young children. In this report, circulating PCV-13 serotype-specific B and T cell memory in paired blood samples from children before and after PCV13 dose 3 and booster immunizations was analyzed to determine changes in the adaptive immune response. No significant differences in memory B cell populations were detected comparing post dose 2 vs. post dose 3. However, the booster dose significantly increased the frequency of Spn-specific memory B cells compared to the pre-booster. Spn-specific memory T cells were not detected with the method used. These data suggest that booster vaccination increases Spn-specific memory B cells that may impact long-term protective antibody titers.